Effects of Soil Water Regulation on Growth and Yield of Fruit Radish under Drip Irrigation in Greenhouse - CHEN Ke; LIU Wenxin; FENG Di; ZHU Haiyan; ZHANG Jingmin; SANG Xiaoming; DING Faqiang; SUN Xiaoan (Guan'gai paishui xuebao, 2023)
【Objective】 The fruit radish is a cash crop commonly cultivated in greenhouses in central and northern China. This study aims to determine the most effective drip irrigation schedule to enhance its yield while simultaneously increasing water use efficiency. 【Method】 The cultivar “Ice Cream” was used as the model plant. The irrigation was based on soil matric potential measured at the depth of 20 cm in that whenever it dropped to -10 (T1), -20 (T2), -30 (T3), -40 (T4) or -50 kPa (T5), we irrigated the crops by 10 mm of water. In each treatment, we measured the growth, yield and quality, as well as irrigation water use efficiency (IWUE) of the crop. 【Result】 The total irrigation amount for T1-T5 decreased from 120 to 70 mm. Reducing the soil matric potential threshold for irrigation resulted in reductions in area and fresh weight of leaves, root diameter and length, and weight of the radish, albeit the reduction in root length was not significant. Compared with T1, T2—T5 increased the yield by 2.2% to 44.0%, T2 increased IWUE by 17.3%, and T3—T5 reduced IWUE by 4.1% to 6.6%. With the decrease in the soil matric potential threshold, the soluble solid content and electrical conductivity of the radish both increased first followed by a decline, the soluble solid content peaked in T2 and Vc content increased monotonically. 【Conclusion】 Setting soil matric potential at depth of 20 cm at -20 kPa as the threshold and the irrigating 10 mm of water each time is optimal for improving the yield and IWUE of greenhouse fruit radish.